Time From Imaging to Endovascular Reperfusion Predicts Outcome in Acute Stroke. Issue 4 (April 2018) - Tsai, Jenny P.; Mlynash, Michael; Christensen, Soren; Kemp, Stephanie; Kim, Sun; Mishra, Nishant K.; Federau, Christian; Nogueira, Raul G.; Jovin, Tudor G.; Devlin, Thomas G.; Akhtar, Naveed; Yavagal, Dileep R.; et al.
Abstract : Background and Purpose—: This study aims to describe the relationship between computed tomographic (CT) perfusion (CTP)-to-reperfusion time and clinical and radiological outcomes, in a cohort of patients who achieve successful reperfusion for acute ischemic stroke. Methods—: We included data from the CRISP (Computed Tomographic Perfusion to Predict Response in Ischemic Stroke Project) in which all patients underwent a baseline CTP scan before endovascular therapy. Patients were included if they had a mismatch on their baseline CTP scan and achieved successful endovascular reperfusion. Patients with mismatch were categorized into target mismatch and malignant mismatch profiles, according to the volume of their Tmax >10s lesion volume (target mismatch, <100 mL; malignant mismatch, >100 mL). We investigated the impact of CTP-to-reperfusion times on probability of achieving functional independence (modified Rankin Scale, 0–2) at day 90 and radiographic outcomes at day 5. Results—: Of 156 included patients, 108 (59%) had the target mismatch profile, and 48 (26%) had the malignant mismatch profile. In patients with the target mismatch profile, CTP-to-reperfusion time showed no association with functional independence ( P =0.84), whereas in patients with malignant mismatch profile, CTP-to-reperfusion time was strongly associated with lower probability of functional independence (odds ratio, 0.08; P =0.003). Compared with patients with target mismatch, those with the malignant mismatch profile had significantly more infarct growth (90 [49–166] versus 43 [18–81] mL; P =0.006) and larger final infarct volumes (110 [61–155] versus 48 [21–99] mL; P =0.001). Conclusions—: Compared with target mismatch patients, those with the malignant profile experience faster infarct growth and a steeper decline in the odds of functional independence, with longer delays between baseline imaging and reperfusion. However, this does not exclude the possibility of treatment benefit in patients with a malignant profile. Abstract : Supplemental Digital Content is available in the text.